Activities contributing to energy expenditure among Guatemalan adults - Martorell Reynaldo; Ramirez-Zea Manuel; Gregory Cria O; Stein Aryeh D (BMC, 2007)
Abstract Background Guatemala has experienced a substantial increase in overweight and obesity in recent years, yet physical activity patterns and consequent energy expenditure are largely unexplored in this population. Methods To describe overall physical activity levels (PAL) and activities contributing to daily energy expenditure, we analyzed time spent in daily activities as reported by 985 women and 819 men, living in rural and urban areas of Guatemala in 2002-04. Results Physical activity levels recommended to prevent obesity (PAL ≥ 1.70) differed by residence/occupation among men (agricultural-rural: 77%; nonagricultural-rural: 36%; urban: 24%; P < 0.01), but not women (rural: 2%; urban: 3%; P = 0.5). Median energy expenditure was higher among agricultural-rural men (44 MET*h/d; MET = metabolic equivalent) compared to nonagricultural-rural (37 MET*h/d) and urban men (35 MET*h/d; P < 0.01); energy expenditure was slightly lower among rural compared to urban women (34 MET*h/d vs. 35 MET*h/d; P < 0.01). Occupation was the largest contributor to energy expenditure (19-24 MET*h/d); among women and nonagricultural-rural and urban men this was primarily of a light intensity. Energy expenditure in sedentary activities ranged from 2 MET*h/d among rural women to 6 MET*h/d among agricultural-rural men. Any sports/exercise time was reported by 35% and 5% of men and women, respectively. Nevertheless, the majority of participants believed they were significantly active to stay healthy. Conclusion Overall, energy expenditure was low in the population not dedicated to agricultural occupations; an increased focus on active leisure-time behaviors may be needed to counterbalance reductions in energy expenditure consequent to sedentarization of primary occupations.